Hubungan Miopia dengan Prestasi Akademik dan Pola Melihat Dekat pada Mahasiswa Fakultas Kedokteran Universitas Riau - Elda Nazriati; Chandra Wijaya (Fakultas Kedokteran Universitas Riau, 2010)
Prevalence rates of myopia in many Asian urban countries reaching epidemic proportion. It has long been observedthat myopic children have higher IQ, and association between myopia and higher level of near work. This study aimsto quantify the association myopia with school achievement and near work in Riau University medical students. Theprevalence rate of myopia in Riau University medical students was 31.4 % (76 students). Myopia students as casesgroup compare to emmetropic students as control group. This study showed that high significant association myopiawith near work profile and no significant association myopia with school achievement. Myopia students more likely tohave risk near work profile than emmetropic students (x2 test P < 0.001) with odds ratio 6.12. Myopia students morelikely to have high GPA than emmetropic students (OR 1.34) but interaction between myopia and school achievementwere not significant (x2 test p> 0.05).